Aetiology, diagnosis and management of heart failure in infants and children - Pepeta, Lungile (SA Heart Journal, 2017)
Heart failure is due to failure of ventricular filling with failure of ejection of blood from the ventricles. It may present as volume overload with ventricular dysfunction, volume overload with preserved ventricular function, and pressure overload. Causes of heart failure in the paediatric age group include both congenital and acquired heart diseases. Dilated cardiomyopathy remains the most common cause of heart failure in the paediatric population. In this article, epidemiology; pathophysiology; aetiology; clinical presentation; investigations including radiological and laboratory investigations; medical and non-medical management of acute, chronic and end-stage heart failure and prognosis will be reviewed.